Produção de blocos de concreto para pavimentação (BCP) utilizando resíduos de galvanoplastia - Franco, Janaina de Melo (2011)
The incorporation of industrial wastes in cement matrix has received great emphasis, especially regarding the stabilization of heavy metal that occurs in the solidification process or interaction aggregate/cement. For this purpose, this study was to evaluate this interaction through the use of electroplating waste (dust from blasting and sludge) in the production of concrete block paving (CBP) analyzing the physical, chemical, mechanical and microstructural resulting the replacement of cement by these residues (5, 10, 15, 20 and 25%) and comparing them with the blocks or blocks without replacement reference. The results of the decks produced with dust from blasting (CBP-PJ) showed a reduction in the absorption of water in all proportions in relation to the blocks used for all ages, including the increase of compressive strength in CBP-PJ5 at all ages with respect to reference blocks. However, the results of leaching and solubilization showed that all ratios and reference blocks, the values of arsenic were found above the limit of NBR 10004/2004, which may be related to the amount of metal found in the analysis performed with cement. The results of using mud blocks (CBP-LG), the compressive strength only CBP-LG5 value above and below the NBR 9781/1987 blocks reference to 28 days, besides the reduction in water absorption with respect to all the other blocks. In solution and leaching tests of samples from the CBP with the sludge, the concentrations of arsenic were reduced substantially depending on the age of healing, when compared with results for CBP-PJ and reference blocks. That is, revealing the promising applicability and technical feasibility of using waste from electroplating in the construction industry.